Inpatient Mortality in Parkinson's Disease. (April 2023) - Phillips, Oliver W.; Kunicki, Zachary; Jones, Richard; Belanger, Emmanuelle; Shireman, Theresa I.; Friedman, Joseph H.; Kim, Duk Soo; Kluger, Benzi; Akbar, Umer
Introduction: Although a majority of the American public prefer to die at home, a large percentage of Parkinson's disease patients die in acute care hospitals. We examine trends in the clinical and demographic characteristics of Parkinson's disease patients who die in a hospital to identify populations potentially vulnerable to unwanted inpatient mortality. Methods: Patients with Parkinson's disease admitted to a hospital from 2002-2016 were identified from the National Inpatient Sample (n = 710, 013) along with their associated clinical and demographic characteristics. The main outcome examined was mortality during inpatient admission. From these data, logistic regression models were estimated to obtain the odds ratios of inpatient mortality among clinical and demographic attributes, and their change over time. Results: Characteristics significantly associated with increased odds of inpatient mortality included increased age (OR = 1.70 for 55-65, 2.52 for 66-75, 3.99 for 76-85, 5.72 for 86+, all P < 0.001), length of stay ≤5 days (reference; 6 + days OR = 0.37, P < 0.001), white race or ethnicity (reference; Black OR = .84 P < .001, Hispanic OR = 0.91 P = 0.01), male (reference; female OR = 0.93 P < 0.001), hospitalization in Northeast (reference; Midwest OR = 0.78, South 0.84, West OR = 0.82; all P < 0.001), higher severity of illness (moderate OR = 1.50, major OR = 2.32, extreme OR = 5.57; all P < 0.001), and mortality risk (moderate OR = 2.88, major OR = 10.92, extreme OR = 52.30; all P < 0.001). Fitted probabilities overall declined over time. Conclusion: Differences exist among PD patient populations regarding likelihood of in-hospital mortality that are changing with time. Insight into which PD patients are most at risk for inpatient mortality may enable clinicians to better meet end-of-life care needs.